Distribution of threshold values of harmfulness of larvae of lamellar phytophages in time - E. Korenchuk; V. Drozda (Карантин і захист рослин)
Goal. Clarification of the threshold of harmful larvae for 2-year-old pine seedlings at different stages of the growing season.